The Contribution of Community Participation, Sustainable Economic Literacy, and Environmental Policy to The Improvement of Waste Bank Performance: a Case Study Of The Waste Bank in Besang Village, Semarapura Kaja - Luh Made Pramita Suriyani; Amrita Nugraheni Saraswaty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Waste management has become a critical issue in efforts to create a clean and sustainable environment, particularly in Klungkung Regency, which has seen a significant increase in waste generation following the COVID-19 pandemic. One of the local government’s initiatives to address this issue is the establishment of waste banks, including the Lestari Waste Bank in Besang Village. This study aims to analyze the influence of community participation, sustainable economic literacy, and environmental policy on the performance of the waste bank. The research was conducted in Besang Village, covering three sub-village areas: Besang Kawan, Besang Tengah, and Besang Kangin, with a total of 182 waste bank customers as respondents. A quantitative approach was employed using multiple linear regression analysis. The findings indicate that community participation significantly contributes to improving the effectiveness of the waste bank program. Furthermore, community understanding of sustainable economic principles influences individual mindsets and waste-sorting behavior. In addition, environmental policies implemented by the local government strengthen the institutional capacity of waste banks to manage waste systematically and sustainably. Therefore, the collaboration between community involvement, economic understanding, and policy support is key to the success of waste banks as a community-based waste management solution.